Aspectos de la Flora y Vegetación del Parque Nacional "Vicente Pérez Rosales" (Llanquihue - Chile) - Martínez M., Osvaldo (Bosque (Valdivia), 1985)
A forest and floristical report of "Vicente Perez Rosales" National Park, located in the Llanquihue province in south central Chile is presented. The three forest types present in the park: Evergreen, Alerce and Lenga, are described. The evergreen type is a forest with Nothofagus dombeyi, Aextoxicon punctatum, Eucryphia cordifolia and Myrtaceae is located between 150 and 500m over sea level. Over 500 m and mainly between 700 and 1.000 m over sea level, Eucryphia cordifolia is substituted by Laurelia philippiana, Dasyphyllum diacanthoides and Weinmannia trichosperma. The Alerce type is very similar to the Evergreen type, but with Fitzroya cuppressoides (Alerce). This species occures in two different habitats: on steep lands, and on moist habitats. Lenga type is located at high altitudes, between 800 and 1.200 m over sea level, with Nothofagus pumilio (Lenga) as the principal tree. Geographical ubication climatic characteristics and a plant catalogue of 152 vascular species are given. The biological spectrum of plant life form is analized, and the most important characteristics of the park’s vegetation are furnished.